PSEUDO-SLANT SUBMANIFOLD IN KENMOTSU SPACE FORMS - Dirik, Suleyman; Atceken, Mehmet; Yildirim, Umit (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper, we study geometry of the pseudo-slant submanifold of a Kenmotsu space form. Necessary and suffcient conditions are given for a submanifold to be a pseudo-slant submanifold in Kenmotsu manifolds. Finally, we give some results for totally umbilical pseudo-slant submanifold in a Kenmotsu manifold and Kenmotsu space form.